A Comprehensive Analysis of Expenditure Decentralization and of the Composition of Local Public Spending. Issue 1 (2nd January 2016) - Sacchi, Agnese; Salotti, Simone
Abstract : Sacchi A. and Salotti S. A comprehensive analysis of expenditure decentralization and of the composition of local public spending, Regional Studies . Many industrialized countries have recently implemented fiscal decentralization reforms assigning more spending responsibility to sub-national governments. This paper investigates the causes of the decentralization of different categories of public expenditure in 19 developed countries over the period 1980–2006. Different models for each of the spending functions under analysis are estimated adopting a general-to-specific empirical approach. Results confirm existing findings on the negative link between regional income disparities and expenditure decentralization. A similarly negative relationship is found for a set of demographic variables, leading to the conclusion that macroeconomic and, more importantly, political factors are responsible for the recent increase in decentralization. Finally, the analysis is completed by a study of the factors driving sub-national expenditure composition, with political and demographic changes emerging as the most important determinants.